Reverberações, o diálogo entre a poesia e o pensamento crítico de Henriqueta Lisboa: um olhar contemporâneo - Túlio César Vieira Alves (2019)
The thesis proposes to analyze Henriqueta Lisboa's critical production in the light of contemporary thinking. The volumes of essays Convívio poético (1955), Vigília poética (1968) and Vivência poética (1979) form Henriqueta Lisboa's critical and theoretical production. They contain the guiding principles of her thinking in comparison with her own poetic production and her gaze on the literary works of other authors. Reflection on the poetic image in comparison with the contemporary concept of image, as well as its unfolding in concepts such as survival, montage and remontage form the main axis of research articulation.